The effectiveness and safety of acupuncture treatment on sciatica: A systematic review and meta-analysis. (December 2022) - Han, Kyou-Hwan; Cho, Ki Haeng; Han, Caroline; Cui, Shanqin; Lin, Lily; Baek, Ho-Yu; Kim, Jaejong
Abstract: Background: Sciatica results from primary or secondary damage to the sciatic nerve in the lumbar or gluteal region. The first option for sciatica is analgesics, but their therapeutic effect and safety in long-term use are questionable. On the other hand, acupuncture has recently been recognized as a complementary and alternative medicine (CAM) to conventional medicine, and studies on its effectiveness and safety have been actively conducted. Objective: To systematically compare acupuncture with analgesics in terms of effect, safety, and durability in the treatment of sciatica Methods: This review was performed in accordance with Cochrane Handbook for Systematic Reviews of Interventions Version 6.2. Four databases were searched for this review: Wangfang, the Korean Traditional Knowledge Portal (KTKP), PubMed, and EBSCOhost. The primary outcome measures in the review were total effective rate (TER), visual analog scale (VAS) score and pain threshold, and the secondary ones were adverse effects (AEs) and relapse rates. Risk ratio (RR) for TER and mean difference (MD) for VAS score and pain threshold were used as statistics for the meta-analysis of effectiveness, along with associated 95 % confidence intervals (CIs) and P-values. AEs and relapse rates were used for the safety and durability of the interventions. Version 2 of the Cochrane risk-of-bias assessment tool for randomized trials (RoB 2) was used for the methodological quality of randomized controlled trials (RCTs) included in the review. Results: The synthesized TER of 28 RCTs involving 2707 participants was significantly higher in the acupuncture group compared to the analgesic group ( RR [95 % CI ] = 1.20 [1.16, 1.24], P < 0.001). The synthesized VAS score of 7 RCTs involving 589 participants was significantly reduced in the acupuncture group compared to the analgesic group ( MD [95 % CI ] = − 1.78 [− 2.44, − 1.12], P < 0.001). In 5 RCTs involving 311 participants, the synthesized pain threshold was significantly elevated in the acupuncture group compared to the analgesic group ( MD [95 % CI ] = 0.93 [0.64, 1.22], P < 0.001). Additionally, adverse effects (AEs) and relapse rates of RCTs in the review were lower in the acupuncture group compared to the analgesic group. Conclusion: In this systematic review, acupuncture treatment was significantly effective and safe compared to analgesics in sciatica. In the future, studies with a rigorous study design are required to increase the validity of the effectiveness and safety of acupuncture treatment for sciatica. Highlights: Sciatica causes movement disorders along with pain in the lower back and hips as well as the legs. The effectiveness and safety of conventional medicines for sciatica are questionable. Acupuncture can be an alternative to conventional medicines for sciatica.